THE FORMATION AND HISTORICAL SIGNIFICANCE OF THE TASHKENT TRADE FAIR (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This article explores the establishment of the Tashkent Trade Fair in the 19th century, analyzing its origins, historical circumstances, early operations, and its contribution to the economic development of the Turkestan Governorate-General. Drawing upon archival documents, historical studies, and modern research, the paper examines how the fair became a vital center of regional trade, linking Central Asia to the Russian Empire and the global market. The study also highlights the fair’s influence on industrialization, infrastructure, and the modernization of local commerce and society.